2019
DOI: 10.3390/ijms20215419
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Long Non-coding RNA in Trifoliate Orange (Poncirus trifoliata (L.) Raf) Leaves in Response to Boron Deficiency

Abstract: Long non-coding RNAs (lncRNAs) play important roles in plant growth and stress responses. As a dominant abiotic stress factor in soil, boron (B) deficiency stress has impacted the growth and development of citrus in the red soil region of southern China. In the present work, we performed a genome-wide identification and characterization of lncRNAs in response to B deficiency stress in the leaves of trifoliate orange (Poncirus trifoliata), an important rootstock of citrus. A total of 2101 unique lncRNAs and 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Further, expression profiling analysis identified 729 up-regulated and 721 down-regulated lncRNAs under B deficiency stress. Functional validation of selected lncRNAs shed light on the target genes involved in the calcium signaling and plant hormone signal transduction pathways under B deficiency stress in Poncirus trifoliata [98].…”
Section: Lncrnas Regulating Nutrient Deficiency In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, expression profiling analysis identified 729 up-regulated and 721 down-regulated lncRNAs under B deficiency stress. Functional validation of selected lncRNAs shed light on the target genes involved in the calcium signaling and plant hormone signal transduction pathways under B deficiency stress in Poncirus trifoliata [98].…”
Section: Lncrnas Regulating Nutrient Deficiency In Plantsmentioning
confidence: 99%
“…Among the various micronutrients, boron (B) is an essential micronutrient for plant growth and development, membrane integrity, and cell wall synthesis [ 137 – 139 ]. Genome-wide exploration of lncRNA regulating B deficiency response in Poncirus trifoliata through strand-specific deep transcriptome analysis detected 2101 unique lncRNAs [ 98 ]. Further, expression profiling analysis identified 729 up-regulated and 721 down-regulated lncRNAs under B deficiency stress.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging evidence suggests that B’s molecular regulation is complicated, limited to coding genes, and attributed to lncRNAs, a novel regulatory player in the regulation of gene expression. A genome-scale exploration of lncRNAs in response to B toxicity detected ~8000 lncRNAs [ 137 ], whereas under B deficiency conditions in P. trifoliata 2101 lncRNAs were detected, of which 729 were upregulated and 721 were downregulated [ 138 ].…”
Section: Role Of Lncrnas In Biotic and Abiotic Stressmentioning
confidence: 99%
“…Therefore, the Fanconi anemia pathway might regulate the proliferation and apoptosis of coronary endothelial cells and smooth muscle cells that are associated with atherosclerotic pathology ( Wolf and Hunziker, 2020 ). Previous research indicated that lncRNA can cis- or trans-regulate the expression of target genes, which is the main regulation mechanism of lncRNA ( Zhou G. F. et al, 2019 ). The coexpressed target genes in our study are on different chromosomes from the correlated lncRNA, which suggest that these lncRNAs trans-regulate the target genes to affect the occurrence and development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%